Artistical Da'wah in the New Normal Era: Visualization of Wayangaji by Miko Cak Coy Pathoknegoro - Rahadiyand Aditya; Istiqomah Istiqomah; Zaenudin Amrulloh (JURNAL ILMIAH SYI'AR, 2021)
The new normal era requires a new approach for every aspect of life. There needs to be various adjustments including religious rituals. Miko Cak Coy Pathoknegoro is a preacher who preaches with puppets as a medium for his preaching. This research looks at how Miko Cak Coy Pathoknegoro preaches in the new normal era. The approach used is qualitative research with interviews and documentation studies as data collection techniques and triangulation of sources and data as data validity techniques. This research concludes that the preaching of Miko Cakcoy is included in contemporary dakwah. Wayangaji is a concept offered in conducting da'wah activities through wayang. The opportunity for Miko to do da'wah activities during the new normal is that Miko has been active in Social Media since 2014, besides that there is also the Miko Cakcoy Goes to School 'Virtual' activity which can be an opportunity for Miko to do da'wah activities in the new normal era. But there is a challenge for Miko, who until now has never done Wayang activities virtually.